Penggunaan Platform Deutsch_Eins untuk Pembelajaran Mandiri Bahasa Jerman Siswa SMA Laboratorium UM - Putri, Princessica Olivia Kersa; Usman, Rizman (Universitas Negeri Malang, 2024)
German language learning in high schools is increasingly vital in the era of globalization. Challenges like student disinterest and the need for self-access to materials persist, notably at UM Laboratory High School. Digital solutions such as the Deutsch_Eins/Deutsch1 platform aim to increase student engagement because it can stimulate students in learning German independently. The formulation of the problem in this study is how the use of the Deutsch_Eins/Deutsch1platform in independent learning of German by UM Laboratory High School students and how students' opinions about the use of the Deutsch_Eins/Deutsch1 platform for independent learning of German. The purpose of this study is to determine the potential use of the Deutsch_Eins/Deutsch1 platform in independent learning of German by UM Laboratory High School students and to find out students' opinions about the use of the Deutsch_Eins/Deutsch1 platform. This research focuses on twelfth grade IBB students, using observation for the process of using the Deutsch_Eins/Deutsch1 platform in class and interviews for student opinions regarding the platform as data collection. Qualitative analysis shows the positive impact of using Deutsch_Eins: easy access via social media, high enthusiasm, the content is quality, and the delivery is easy to understand. The result of this study shows that Deutsch_Eins/Deutsch1 can help students learn German easily and fun. In addition, it also increases students' interest and motivation in learning German independently.